In vitro evaluation of the effects of 4-aminopyridine on cytochrome P450 enzymes. (23rd April 2013) - Caggiano, Anthony; Blight, Andrew
Abstract: Background: Dalfampridine extended release tablets (dalfampridine-ER, known as prolonged-, modified, or sustained-release fampridine tablets in some countries) are approved for the improvement of walking in patients with multiple sclerosis (MS). Dalfampridine-ER is an extended release formulation of 4-aminopyridine (4-AP). Dalfampridine-ER is incorporated into MS management strategies that may include disease-modifying and symptomatic therapies. Since several symptomatic therapies are partially or fully metabolized by enzymes of the hepatic cytochrome P450 system (CYP450) it is important to evaluate drug–drug interactions through potential effects of dalfampridine-ER on CYP450. Methods: The ability of 4-AP to inhibit CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1, and CYP3A4/5 in a direct and time-dependent manner was evaluated using pooled human liver microsomes. 4-AP concentrations were 0.03, 0.1, 0.3, 1, 3, 10, and 30 μM, representing 0.1–100-times the average plasma 4-AP concentration (30 ng/mL; 0.32 μM) at therapeutic dosing; the concentration inhibiting 50% of each enzyme activity (IC50 ) was determined. The ability of 4-AP (0.025, 0.25, 2.5, and 25 μM) to induce the expression of CYP1A2, 2B6, 2C9, 2C19, 2E1, and 3A4/5 enzymes was evaluated using primary cultures of freshly isolated human hepatocytes from non-transplantable livers. The enzyme-inducing effects of 4-AP were compared with the prototypical inducers. Metabolites were assayed using high-performance liquid chromatography-tandem mass spectrometry techniques. All inhibition and induction assays included positive controls. Results: 4-AP did not directly inhibit CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, or CYP3A4/5, but at a concentration of 30 μM, CYP2E1 was inhibited by 12%, resulting in an estimated IC50 value of 125 μM. None of the enzymes demonstrated time-dependent inhibition by 4-AP. There was little or no effect by 4-AP on enzyme induction, with enzyme activities approximately equivalent to vehicle control. A main limitation was the inability to estimate effectiveness of 4-AP relative to prototypical CYP450 inducers. Conclusion: The likelihood of drug–drug interactions is remote in patients with MS who may be taking dalfampridine-ER concomitantly with medications that are metabolized by CYP450 pathways.